Multiservice Infrastructure : Privatizing Port Services - Trujillo, Lourdes (World Bank, Washington, DC, 2012)
Ports have become increasingly capital intensive. Economies of scale have led to larger, more specialized ships, and, competition between ports has started to grow. As a result, governments are reorganizing the way ports are run, and permitting more private ownership, and service delivery. Because ports provide multiple services, if governments are to design an efficient legal, and regulatory framework for private participation, it is important to study all these activities to evaluate the best approach. Moreover, because these activities must take place in a small space, it is important to study how they are best coordinated. The note outlines privatization options, such as: full privatization, i.e., all assets and liabilities are transferred to the private sector; build, operate and own, i.e., parts of the port are sold to be developed; build or rehabilitate, on a concession basis; joint ventures; leasing, i.e., no investments, only commercial risks; licensing, (provision of equipment); and, management contract, i.e., both investment and commercial risks are faced by the public sector.